The Lean Product Design and Development Journey A Practical View - Pessôa, Marcus Vinicius Pereira; Trabasso, Luis Gonzaga; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents a series of high performance product design (PD) and development best practices that can create or improve product development organization. In contrast to other books that focus only on Toyota or other individual companies applying lean IPD, this book explains the lean philosophy more broadly and includes discussions of systems engineering, design for X (DFX), agile development, integrated product development, and project management. The "Lean Journey" proposed here takes a value-centric approach, where the lean principles are applied to PD to allow the tools and methods selected to emerge from observation of the individual characteristics of each enterprise. This means that understanding lean product development (LPD) is not about knowing which tools are available but knowing how to apply the philosophy. The book comes with an accompanying manual with problems and solutions available on Springer Extras.
Part I: The Track -- 1. The Product Development System -- 2. Integrated Product Design and Development -- 3. Lean Thinking -- Part II: The Wheel Hub -- 4. Continuous Improvement -- 5. Value on Product Development -- 6. Waste on Product Development -- Part III: The Wheel -- 7. The Lean Product Development Organization Culture -- 8. The Lean Product Development Organization Knowledge Management -- Part IV: The Tire -- 9. The Lean Product Development Process -- 10 -- Study Phase - Value Identification Activities -- 11. Study Phase - Value Proposition Activities -- 12. Study Phase - Value Delivery Planning Activities -- 13. Execution Phase -- Part V: On the Road -- 14. Bumps on the Track -- 15. Thermo Baby Development Project -- 16. SIVOR Development Project.
Keywords: Industrial engineering; Production engineering; Technological innovations; Engineering design; Electronic data processing -- Management; Automotive engineering; Industrial and Production Engineering; Innovation and Technology Management; Engineering Design; IT Operations; Automotive Engineering